2022
DOI: 10.1038/s41536-022-00239-2
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma loaded nerve guidance conduit as implantable biocompatible materials for recurrent laryngeal nerve regeneration

Abstract: Vocal cord paralysis caused by recurrent laryngeal nerve (RLN) injury during thyroidectomy results in hoarseness, aspiration, and dyspnea. We evaluated the usefulness of nerve guidance conduits (NGCs) constructed from an asymmetric polycaprolactone (PCL)/Pluronic F127 porous membrane and filled with platelet-rich plasma (PRP) for functional RLN regeneration. We evaluated the proliferation and migration of Schwann cells (SCs) after PRP treatment in vitro. For the in vivo study, rabbits were divided into a non-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…The extracellular milieu of the surviving neurons was improved by 59 , 61 , demonstrating that the brain trophic factor BDNF-modified human BMSCs exhibited additive neuroprotective effects and that accelerated axonal sprouting NGF expression was higher in PRP-treated cells than in untreated controls. NGF expression was higher in the treated cells than in the untreated controls 62 , 63 which coincides with our results.…”
Section: Discussionsupporting
confidence: 92%
“…The extracellular milieu of the surviving neurons was improved by 59 , 61 , demonstrating that the brain trophic factor BDNF-modified human BMSCs exhibited additive neuroprotective effects and that accelerated axonal sprouting NGF expression was higher in PRP-treated cells than in untreated controls. NGF expression was higher in the treated cells than in the untreated controls 62 , 63 which coincides with our results.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, a variety of substances including collagen fibers, stem cells, and neurotrophic factors like nerve growth factor have been found to enhance regeneration of injured peripheral nerves. 41 Although stem cells implantation in NGCs have demonstrated useful effects on THE regeneration of injured peripheral nerves, but it has been found that the key critical mechanism for stem cells in peripheral nerve repair refers to the paracrine effect of stem cells rather than the differentiation potency of stem cells. 24 Additionally, many studies have demonstrated that the paracrine role of stem cells is related to their released exosomes as cell products.…”
Section: Discussionmentioning
confidence: 99%
“…So, this study was proved that the double layered SF/PLLA nerve guide conduit had acceptable biocompatibility and mechanical properties and can support cell attachment along with proliferation. Additionally, a variety of substances including collagen fibers, stem cells, and neurotrophic factors like nerve growth factor have been found to enhance regeneration of injured peripheral nerves . Although stem cells implantation in NGCs have demonstrated useful effects on THE regeneration of injured peripheral nerves, but it has been found that the key critical mechanism for stem cells in peripheral nerve repair refers to the paracrine effect of stem cells rather than the differentiation potency of stem cells .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, animal studies have shown that various neurotrophic factors are expressed during nerve rupture 3,4 . As one of them, the glial cell line‐derived neurotrophic factor (GNDF) is up‐regulated after nerve injury, stimulates Schwann cell migration and promotes myelination 3,29–31 . It is conceivable that similar changes in neurotrophic factors occur after RLN injury 28,32–34 .…”
Section: Discussionmentioning
confidence: 99%